THE BARGONASCO - UPPER VAL GRAVEGLIA OPHIOLITIC SUCCESSION, NORTHERN APENNINES, ITALY - Bortolotti, Valerio; Principi, Gianfranco (Ofioliti, 2003)
The Northern Apennines ophiolitic successions pertain to the Ligurian orogenic units, which were thrust onto the Adria continental margin (Tuscan and Umbrian Units) and show two different types of stratigraphic settings (Fig. 1) (Abbate et al., 1980):a- as “oceanic basement” of the Vara Supergroup, one of the higher units of the tectonic pile (“Internal Ligurides”);b- as olistoliths of variable sizes, accompanied by ophiolitic breccias, included in the Upper Cretaceous - Eocene terrigenous successions of the “External Ligurides” tectonic units.The Val Graveglia-Bargonasco area represented in the map, is located in eastern Liguria, on the northwesternmost side of the Northern Apennine, where most and more complete ophiolitic sequences of type a- crop out (the “Mt. Porcile Unit, Fig. 1). They consist of mantle peridotites (from clinopyroxene-poor lherzolites to harzburgites) and gabbros, which form the “oceanic basement”, metamorphosed and tectonically denudated before the volcano-sedimentary cover (ophiolitic breccias, basalts, cherts, carbonate and carbonate- shaly pelagites, and finally siliciclastic turbidites) was deposited.The tectonic scheme (Fig. 1, partially modified from the “schema tettonico” of the geologic map) shows that the Porcile Unit, object of our study, includes seven subunits separated by minor thrusts, i.e., from west to east, Mt. Domenico, M. Bianco, Rio Gromolo, Mt. Ciazze, M. Bocco, Rivo Orti, Mt. Tregin Subunits. The stratigraphic successions of all the Subunits pertain to the Vara Supergroup (see the stratigraphic Scheme on the geologic map).This short note summarises a more extensive one, about the geologic evolution of this same area, which will be published in the Atti Ticinensi di Scienze della Terra, Pavia, Italy, 2004. We decided to write this short summary to advertise the map of this key area for understanding the geology of the Northern Apennine ophiolites.